Anesthetic Efficacy of Intraligamentary Injection Techniques on Mandibular Posterior Teeth Diagnosed with Asymptomatic Irreversible Pulpitis - ., Avinash; Sheikh, Abu Bakar; Rashid, Saqib; Ali, Muhammad; Siddiqui, Kishwer Naz; Mujeeb, Fauzia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of Intraligamentary Injection with the IANB injection technique for root canal treatment of mandibular molars and premolars in patients with asymptomatic irreversible pulpitis undergoing access opening. Study Design: Quasi-experimental study. Place and Duration of Study: Operative Dentistry Department, Fatima Jinnah Dental College Karachi Pakistan, from Nov 2018 to Apr 2019. Methodology: The study was conducted on 80 patients. Visual analogue scale was used to determine the level of pain. Three groups were made depending on the effectiveness of anaesthesia at 2-sites (Group-A), 4-site (Group-B) and failure of Intraligamentary injection (Group-C). Anaesthesia was successful when the patient revealed no pain symptoms during access opening. Results: A total of 80 cases were evaluated, out of which 47 were males (58.70%), and 33 were females (41.30%). The most common age groups recorded in our study were 18 – 25 years (33.75%) and 36- 45 years (33.75%). According to our results, the Intra-ligamentary technique was successful in 23(28.75%) cases. The remaining 57(71.25%) cases which received anaesthesia via IANB showed a 100.00% success rate with profound anaesthesia. Conclusion: Inferior alveolar nerve block was more successful compared to Intraligamentary injections for providing profound anaesthesia to mandibular posterior teeth previously diagnosed with asymptomatic irreversible pulpitis and under-going the procedure of access opening.